Nonresonant Polarized Raman Spectra Calculations of Nitrogen-Doped Single-Walled Carbon Nanotubes: Diameter, Chirality, and Doping Concentration Effects - F. Allali; H. Chadli; M. Bentaleb; P. Hermet; A. Rahmani (The Scientific World Journal)
Raman spectra of nitrogen-doped single-walled carbon nanotubes are calculated using the spectral moment’s method combined with the bond polarizability model. The influence of the nanotube diameter and chirality is investigated. We also address the important question of the effect of the N-doping concentration, and we propose an equation to estimate the doping concentration from the knowledge of the tube diameter and the frequency of the radial breathing mode.